2013
DOI: 10.1177/0306624x13479935
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Delinquency and Antisocial Tendencies as Precursors to Adult Violent Offending

Abstract: Studies on adult sex and violent offenders have found high rates of adolescent delinquency, while early delinquency has been shown to be significantly associated with adult offending. The examined subsample (n = 123) of a longitudinal prospective study (n = 6,315) includes all men who at the age of 19 had an entry in the criminal records. During the observation period of 34 years, 68.3% of the sample had been reconvicted as adults, 23.6% for violent or sex offenses. The odds of adult sex or violent offending w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…This group only made up around 5% of the sample, but respondents in this group engaged in high levels of violence from adolescence into early adulthood. Similarly, results from a study of Swiss males found that a higher number of violent offenses in adolescence was predictive of violent recidivism in adulthood (Laubacher et al, 2014).…”
Section: Violent Behavior In Mid-adolescence and Patterns Of Offending In Early Adulthoodmentioning
confidence: 84%
See 2 more Smart Citations
“…This group only made up around 5% of the sample, but respondents in this group engaged in high levels of violence from adolescence into early adulthood. Similarly, results from a study of Swiss males found that a higher number of violent offenses in adolescence was predictive of violent recidivism in adulthood (Laubacher et al, 2014).…”
Section: Violent Behavior In Mid-adolescence and Patterns Of Offending In Early Adulthoodmentioning
confidence: 84%
“…Support for the idea that early violence can result in chronic offending is found in research assessing longitudinal patterns of violent behavior into adulthood (Elliott, 1994;Laubacher et al, 2014;Loeber et al, 2008;Nash & Kim, 2005). In one study, Loeber et al (2008) used data from the youngest and oldest cohorts of the Pittsburgh Youth Study to assess offending specialization.…”
Section: Violent Behavior In Mid-adolescence and Patterns Of Offending In Early Adulthoodmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, all forms of IPV were significantly positively interrelated. Both history of juvenile detention and trait anger (Norlander & Eckhardt, 2005) have been shown to significantly correlate to externalizing behavior and violence variables in several previous studies (Laubacher et al, 2014; Norlander & Eckhardt, 2005). Intercorrelations among the main study variables and demographic variables, including age, race, educational level, and income, were also conducted.…”
Section: Resultsmentioning
confidence: 80%
“…Factors that may increase the likelihood that an individual who engaged in juvenile delinquency will be violent in adulthood also include low parental control and monitoring (Scholte, 1999). Interestingly, a longitudinal study found that characteristics of juvenile delinquency (e.g., versatility, frequency, and severity) predicted adult violent and sexual offending over and above socioeconomic and psychiatric characteristics (Laubacher et al, 2014). However, this study limited its scope of psychiatric characteristics to (a) anxiety, depressive, compulsive-obsessive, and/or sexual neurosis; (b) enuresis; (c), mania and melancholia; (d) schizophrenia; (e) asocial personality and/or antisocial, criminal tendencies; and (f) substance dependence.…”
Section: Juvenile Delinquency and Externalizing Problemsmentioning
confidence: 99%